Perayaan Iman di Usia Tua: Pengembangan Model Pastoral Edukatif di Panti Jompo Katolik Graha Werdha Marie Joseph Pontianak - Adi Ria Singir Meliyanto (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2025)
This study aims to design a contextual and educational pastoral model, assess its level of acceptance, and analyze the positive impact it brings both to the elderly as the service recipients and to students as pastoral partners in the life of the Church. The background of this research lies in the need for a more personal, participatory pastoral approach that touches the emotional and spiritual dimensions of elderly individuals living in Catholic nursing homes. Elderly people often experience loneliness, isolation, and a decline in life motivation. Meanwhile, Catholic students need tangible opportunities to live out their faith values through real actions. The research method employed is Research and Development (R&D), comprising stages such as preliminary study, model design, expert validation, limited trials, and evaluation. The model developed consists of a contextual Liturgy of the Word involving students as Scripture readers, prayer leaders, musicians, and givers of symbolic gifts of love, such as rosaries, to the elderly. The results of the study show that the model was enthusiastically received by the elderly, who expressed joy, active participation in the service, and showed behavioral changes such as praying independently at night and increased social interaction. On the other hand, students experienced growth in faith, empathy, and a deeper awareness of the meaning of service. Therefore, this model is considered appropriate for implementation as part of pastoral care for the elderly and integrated faith formation for the younger generation within the broader context of the Church.